Big Red Tequila - Riordan, Rick (New York Bantam Books, 1997)
A man comes home to San Antonio, Texas, to rescue his old girlfriend and solve the 12-year-old murder of his sheriff father.
113654
Keywords: Private investigators; San Antonio (Tex.); Thrillers (Fiction); Detective and mystery fiction